Psychometric validity of the Thai version of the Motivation for Healthy Eating Scale in patients with acute coronary syndrome - Ratchadaporn Boonsanong; Rapin Polsook (Belitung Raya Foundation, Indonesia, 2023)
Background: Motivation plays a crucial role in lifestyle modifications for disease control and preventing recurrent cardiac events. Higher motivation levels are associated with improved health outcomes, including adherence to a healthy diet and sustained behavior change. However, there is a lack of evaluation of instruments for assessing motivation to adhere to diet recommendations, specifically among patients in Thailand. Objective: This study aimed to assess the psychometric validity of the Thai version of the Motivation for Healthy Eating Scale (MHES) in patients with acute coronary syndrome in Thailand. Methods: The study was conducted between May and August 2022, involving 200 patients with acute coronary syndrome selected through multistage random sampling from tertiary care institutions in Bangkok, Thailand. The scale was translated from English to Thai using the back-translation method. Principal Component Analysis (PCA) and Cronbach's alpha were employed to evaluate the validity and reliability of the scale. Results: The Thai version of the MHES demonstrated satisfactory reliability with a Cronbach's alpha coefficient of 0.73. The analysis revealed four factors consisting of 16 items: 1) ‘integrated and integrated regulation’ with seven items, 2) ‘intrinsic and external regulation’ with three items, 3) ‘introjected regulation’ with three items, and 4) ‘amotivation’ with three items. These factors collectively explained 66.78% of the total variance. Conclusion: The findings indicate that the Thai version of the MHES is a reliable and valid instrument for assessing motivation related to dietary behavior among Thai patients with acute coronary syndrome. Nurses and healthcare professionals can use this scale to evaluate the motivation of dietary behavior among this population, thereby facilitating targeted interventions and promoting positive health outcomes.